2014
DOI: 10.1186/1475-2875-13-392
|View full text |Cite
|
Sign up to set email alerts
|

Global and local genetic diversity at two microsatellite loci in Plasmodium vivax parasites from Asia, Africa and South America

Abstract: BackgroundEven though Plasmodium vivax has the widest worldwide distribution of the human malaria species and imposes a serious impact on global public health, the investigation of genetic diversity in this species has been limited in comparison to Plasmodium falciparum. Markers of genetic diversity are vital to the evaluation of drug and vaccine efficacy, tracking of P. vivax outbreaks, and assessing geographical differentiation between parasite populations.MethodsThe genetic diversity of eight P. vivax popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Results based on NJ tree, MDS and structure analyses reveals patterns of population genetic structure that are consistent with previous studies (e.g. [16][17][18][19][20][21]). The South East Asian populations are the most diverse populations as measured by allelic richness and genetic diversity Hs and present the lowest levels of multilocus linkage disequilibrium (Fig 2).…”
Section: Worldwide Genetic Structure Of P Vivaxsupporting
confidence: 89%
See 1 more Smart Citation
“…Results based on NJ tree, MDS and structure analyses reveals patterns of population genetic structure that are consistent with previous studies (e.g. [16][17][18][19][20][21]). The South East Asian populations are the most diverse populations as measured by allelic richness and genetic diversity Hs and present the lowest levels of multilocus linkage disequilibrium (Fig 2).…”
Section: Worldwide Genetic Structure Of P Vivaxsupporting
confidence: 89%
“…In recent years, due to the importance of understanding the demography of populations, the migration patterns as well as the evolutionary history of the parasite, there has been increased interest in describing the distribution of genetic variation in the global P. vivax population. Several studies on P. vivax have been published, from those focusing on a small set of genetic markers to those describing population genetic structure at the scale of the entire genome (including [16][17][18][19][20][21]). Although these studies all brought their set of information, none of them was able to describe the relationship and the diversity of P. vivax populations over the entire range including East and Western African strains.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous STR-based study of P . vivax diversity in populations from Afghanistan and Pakistan revealed extensive diversity ( H E = 0.98) [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Multiplicity of infection (MOI) refers to the average number of distinct parasite genotypes concurrently infecting a patient and was calculated using the number of different alleles at each locus; single infections were reported by only one allele per locus at all of the genotype loci. 10,14,22 We measured intra-and interpopulation diversity using the statistic expected heterozygosity (He) of each locus, which may be defined as the average probability that two alleles randomly obtained for each locus are different. We calculated the expected heterozygosity using…”
Section: Methodsmentioning
confidence: 99%
“…Studies of P. vivax using microsatellite markers in populations from endemic areas of South America such as the Amazon jungle of Colombia, Brazil, and Peru revealed high levels of heterogeneity (He = 0.44-0.80) and strong differentiation in P. vivax populations. [10][11][12][13][14][15] In Peru, the analysis of the genetic variability and population structure of P. vivax populations using microsatellite markers has been described for the Peruvian Amazon Basin only. 10,16,17 Van den Eede et al, 10 found high levels of genetic variability, highly structured populations, and strong genetic differentiation.…”
Section: Introductionmentioning
confidence: 99%